Clinical and diagnostic aspects of Crohn Syndrome (Research, Society and Development, 2022)
Crohn's disease (CD) is an inflammatory bowel disease that affects part of the population between 20 and 50 years of age, of both sexes. This disease affects people from different socioeconomic classes and nationalities, and affects approximately 1.4 million of people in the United States only. This work aims to talk a little about the disease and report possible complications, diagnosis and treatment of the disease. This review is intended to help bring more knowledge about the disease using the set of several articles to confirm the information. The work developed is an exploratory study, carried out through a systematic review research. According to Marconi and Lakatos (2011), a systematic search covers the entire bibliography already made public in relation to the subject of study. The search strategy used to obtain the articles was the important databases in the health area, with MEDLINE (Medical Literature Analysis and Retrieval System), Science Direct and SCIELO (Scientific Electronic Library Online), ARCA (Fiocruz Institutional Repository), Lilics available online in full text, published in Portuguese (Brazil), English and Spanish. The following descriptors were applied: AUTOIMMUNE DISEASE, CROHN'S DISEASE, INTESTINE SYNDROME. A total of 10,050 articles were found in the scientific databases: Latin American and Caribbean Literature on Health Sciences (LILACS), MEDLINE (Medical Literature Analysis and Retrieval System), Science Direct and SCIELO (Scientific Electronic Library Online), ARCA (Repository Institutional of Fiocruz), Lilics. The following descriptors were used: AUTOIMMUNE DISEASE, CROHN'S DISEASE, INTESTINE SYNDROME, in English, Portuguese and Spanish. Where we obtained the articles described below in table 1 and discussed in the form of topics related to the topic. The present study shows that there are still many problems in identifying the disease, as most doctors research infectious diseases, but this disease, although mysterious, has treatment and diagnosis, which are already used in everyday life and need to be improved for a better quality of life for patients.